Ruinous creatures : a novel - Jackson, Jessi Cole (Atria Books, 2026)
"She tilts her head for me, and I kiss up her neck. It isn't enough. I want her. All of her. In one quick move, without a thought for consequences, I remove her ill-fitting mask. Yes! I hear in my head at the exact same moment she cries out, "No!" It's too late. I have a mere moment to enjoy her beauty. A second later, the world flashes gold, then goes dark." --